Yield Optimization of Display Advertising with Ad Exchange - Balseiro, Santiago R.; Feldman, Jon; Mirrokni, Vahab; Muthukrishnan, S. (Management science, 2014)
It is clear from the growing role of ad exchanges in the real-time sale of advertising slots that Web publishers are considering a new alternative to their more traditional reservation-based ad contracts. To make this choice, the publisher must trade off, in real-time, the short-term revenue from ad exchange with the long-term benefits of delivering good spots to the reservation ads. In this paper we formalize this combined optimization problem as a multiobjective stochastic control problem and derive an efficient policy for online ad allocation in settings with general joint distribution over placement quality and exchange prices. We prove the asymptotic optimality of this policy in terms of any arbitrary trade-off between the quality of delivered reservation ads and revenue from the exchange, and we show that our policy approximates any Pareto-optimal point on the quality-versus-revenue curve. Experimental results on data derived from real publisher inventory confirm that there are significant benefits for publishers if they jointly optimize over both channels. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2014.2017 . This paper was accepted by Dimitris Bertsimas, optimization.